Pelatihan Manajemen Pemasaran dan Branding bagi Pengelola Homestay dan Penginapan Keluarga - Fitria Marisya; Hatidah Hatidah; Marsinah Marsinah; Rolia Wahasusmiah; M Bambang Purwanto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This community service activity aims to improve the knowledge and skills of homestay and family inn managers in marketing and branding management in the region Pagaralam City. The background of this activity is the importance of the role of homestays and family lodging in supporting local tourism, as well as the problems faced by managers in terms of marketing and branding. The method of implementing this activity includes a needs survey, preparation of training materials, training implementation, and follow-up in the form of mentoring and evaluation. The training was attended by 50 participants with a high level of attendance and activity. The results of the pre-test and post-test evaluations showed an average increase of 89 percent in participants' understanding. Feedback from participants also showed that this training was very useful and relevant. After the training, participants began to implement changes in their marketing and branding strategies, which had an impact on increasing the number of guests and the quality of photos of lodging products. The interpretation of the results showed that this training was effective in improving the knowledge and skills of the participants, as well as having a positive impact on their efforts. The conclusion of this activity is that marketing and branding management training has succeeded in increasing the capacity of homestay and family inn managers in developing their businesses. This activity also contributes positively to the development of local tourism.